Renewable energy development in Hungary - Nagy, Orsolya (Acta Agraria Debreceniensis, 2012)
Due to the exhaustion of the fossile fuel reserves of the Earth, the increase of fossile fuel prices and the difficulties concerning stable fuel supply, the increase of electricity production from renewable energy sources has a special strategic importance. In this study, I am going to evaluate the circumstances of the production and use of renewable energy sources in Hungary and in the European Union. I present the Hungarian economic, energy policy-related and social circumstances which make it necessary to support renewable energy production. I am going to give an overview on the related EU strategies concerning the sector and the Hungarian development plan in this field. I pay particular attention to the examination of development opportunities and the R&D activities going on in this area in Hungary, as well as the efficiency of the means used to improve renewable energy use.